2002
DOI: 10.22358/jafs/67807/2002
|View full text |Cite
|
Sign up to set email alerts
|

Associations between bovine milk protein genotypes and haplotypes and the breeding value of Polish Black-and-White bulls

Abstract: One hundred forty three proven Polish Black-and-White bulls were genotyped for 6 polymorphic sites located within 4 milk protein genes (LGB-R promoter, LGB exon IV, CASK-R promoter, CASK exon IV, LALBA 5' flanking region and CSN1S1 promoter). All bulls were divided into groups, including animals with the same genotypes, intragenic haplotypes and combinations of genotypes. For each group, the arithmetic mean and standard deviation for Type Production Index (TPI) and Predicted Transmitting Ability (PTA) (milk kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 15 publications
2
26
1
Order By: Relevance
“…The highest protein content was found in the genotype combinations BBAA, ABBB and ABAB, which illustrates the effect of CSN3 allele B on increasing protein content (Ikonen et al, 1999b;Kučerová et al, 2006). Similarly, Kaminski et al (2002) reported the highest protein content as well as fat content associated with genotype combinations ABBB and ABAB.…”
Section: Fifteen Genotype Combinations Of Csn3 Andmentioning
confidence: 74%
See 2 more Smart Citations
“…The highest protein content was found in the genotype combinations BBAA, ABBB and ABAB, which illustrates the effect of CSN3 allele B on increasing protein content (Ikonen et al, 1999b;Kučerová et al, 2006). Similarly, Kaminski et al (2002) reported the highest protein content as well as fat content associated with genotype combinations ABBB and ABAB.…”
Section: Fifteen Genotype Combinations Of Csn3 Andmentioning
confidence: 74%
“…At corresponding positions, allele B encodes glycine and alanine (Eigel et al, 1984). Allele B was reported to increase milk protein and milk fat contents, while allele A increases milk and protein yields (Neubauerová, 2001;Kaminski et al, 2002;Kučerová et al, 2006). In Czech Fleckvieh cows, Hanuš et al (1995) found a positive effect of the BB genotype on milk coagulation properties, whereas higher curd production due to allele B was reported by Choi and Ng-Kwai-Hang (2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PIT-1). Statistically significant associations between polymorphisms in these genes and milk production traits have been found (Kamiński et al, 2002;Liefers et al, 2002;Zwierzchowski et al, 2002;Maj et al, 2004;Kulig, 2005). Other genes of interest in this area include genes encoding enzymes which participate in fatty acid metabolism as well as genes encoding fatty acid binding and transport proteins (Hradecká et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on milk protein genes and their relation to milk production parameters and milk protein quality focused on single marker effects Ng-Kwai-Hang, 1998;Ikonen et al, 1999;Choi and Ng-Kwai-Hang, 2002). Other studies focused on the effects of haplotypes (Ikonen et al, 2001;Boettcher et al, 2004), or effects of sire genotypes (Ron et al, 1994;Sabour et al, 1996;Kaminski et al, 2002;Kučerová et al, 2006).…”
mentioning
confidence: 99%